Maternal body mass index and access to antenatal care: a retrospective analysis of 619,502 births in England - Charlotte Barber; Judith Rankin; Nicola Heslehurst (BMC, 2017)
Abstract Background Late access to antenatal care increases risks of adverse outcomes including maternal and perinatal mortality. There is evidence that BMI influences patient engagement with health services, such as cancer screening services and delayed access to treatment; this association has not been fully explored in the context of antenatal care. This study investigated the association between the stage of pregnancy women access antenatal care, BMI, and other socio-demographic factors. Methods Retrospective analysis of routine hospital data from 34 NHS maternity units in England, UK, including 619,502 singleton births between 1989 and 2007. Analyses used logistic regression to investigate the association between maternal BMI categories and stage of pregnancy women accessed antenatal care. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were used to estimate associations, adjusting for maternal age, ethnic group, parity, Index of Multiple Deprivation score and employment status. The primary outcome was late access to antenatal care (>13+6 weeks). Secondary outcomes were trimester of access, and the association between late access and other socio-demographic variables. Results Women with an overweight or obese BMI accessed antenatal care later than women with a recommended BMI (aOR 1.11, 95%CI 1.09-1.12; aOR 1.04, 95%CI 1.02-1.06 respectively), and underweight women accessed care earlier (aOR 0.77, 95%CI 0.74-0.81). Women with obesity were 42% more likely to access care in the third trimester compared with women with a recommended BMI. Additional significant socio-demographic associations with late access included women from minority ethnic groups, teenagers, unemployment and deprivation. The greatest association was observed among Black/Black British women accessing care in the third trimester (aOR 5.07, 95% CI 4.76, 5.40). Conclusions There are significant and complex socio-demographic inequalities associated with the stage of pregnancy women access maternity care, particularly for women with obesity accessing care very late in their pregnancy, and among BME groups, teenagers, deprived and unemployed women. These populations are at increased risk of adverse maternal and fetal outcomes and require support to address inequalities in access to antenatal care. Interventions to facilitate earlier access to care should address the complex and inter-related nature of these inequalities to improve pregnancy outcomes among high-risk groups.